2020
DOI: 10.1111/ajps.12549
|View full text |Cite
|
Sign up to set email alerts
|

The Divide Over Independence: Explaining Preferences for Secession in an Advanced Open Economy

Abstract: Anticipated trade, insurance, and fiscal shocks from independence structure preferences for secession independently from nonmaterial considerations. To test this claim, we draw from an original survey conducted in Catalonia before the 2017 regional election, which followed a suspended declaration of independence. Trade shocks produce differential effects depending on market specialization: Respondents working in sectors and at firms specializing in the host state market disproportionately oppose secession, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…In a subsequent analysis, Oller et al (2020) suggested the additional, although relatively minor, influence of economic segmentation on the differential alignments in favour of or against secession. These findings were fully confirmed by surveys exploring the role of material interests in preferences for secession (Hierro and Queralt 2021) and through detailed analyses of recent electoral results (Llaneras 2021). Miley (2007) had already established that the operation of divergent modes of national identification in Catalonian society rested on an ethnolinguistic gap.…”
Section: Introductionmentioning
confidence: 68%
“…In a subsequent analysis, Oller et al (2020) suggested the additional, although relatively minor, influence of economic segmentation on the differential alignments in favour of or against secession. These findings were fully confirmed by surveys exploring the role of material interests in preferences for secession (Hierro and Queralt 2021) and through detailed analyses of recent electoral results (Llaneras 2021). Miley (2007) had already established that the operation of divergent modes of national identification in Catalonian society rested on an ethnolinguistic gap.…”
Section: Introductionmentioning
confidence: 68%
“…Some recent work has tried to address them. Hierro and Queralt (2020) show that respondents working at sectors and firms specializing in the Spanish market are more reluctant toward independence, while those specializing in foreign markets are no more opposed. They also find an association with skill levels that they attribute to a better understanding of the institutional context of redistribution and hence a higher skepticism with regards to the possibilities of accommodation of regional demands within Spain.…”
Section: Discussionmentioning
confidence: 94%
“…The anti-austerity protests in Catalonia also influenced the movement's agenda that, in turn, reshaped its social bases. Hierro and Queralt (2020) provide a more nuanced account of the individual materialist reasons behind the independence push. They show how trade factors are relevant, especially for depressing support among those that work in firms and sectors oriented to the Spanish market.…”
Section: Introductionmentioning
confidence: 99%
“…On practical terms, scholars including Bartkus (2004), Beissinger (2002), and Bishai (2004) have inquired why secessionist demands emerge, while Butt (2017) focused on why some states respond with violence, while others employ concessions. Rodon and Guinjoan (2018) and Hierro and Queralt (2020) developed individual‐level approaches focusing on the identity, the social interactions and the professional occupation of the individual in order to explain public support for, or rejection of, secession.…”
Section: Secession and Declarations Of Independencementioning
confidence: 99%